Tarrying with the negative : Kant, Hegel, and the critique of ideology - Žižek, Slavoj (Post-contemporary interventions., 1993)
A theoretical analysis of social conflict that uses examples from Kant, Hegel, Lacan, popular culture and contemporary politics to critique nationalism.